PENGARUH HARGA DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PENGGUNA DALAM MENINGKATKAN LOYALITAS PENGGUNA LAYANAN GOFOOD DALAM APLIKASI GOJEK DI FAKULTAS EKONOMI UNIVERSITAS WIDYAGAMA MAHAKAM SAMARINDA - Robby Cahyadi (OBOR: Oikonomia Borneo, 2019)
This study aims to determine the extent of the influence of price and service quality on satisfaction in order to increase the loyalty of users of the Go-Jek application based on Gofood at the Faculty of Economics, WidyaGama Mahakam University, Samarinda. The hypotheses tested are (1) there is a significant effect of price on the satisfaction of users of the Gojek application based on Gofood. (2) There is a significant effect of service quality on the satisfaction of users of the Gojek application based on Gofood. (3) There is a significant effect of price and quality of service together on user satisfaction. (4) And there is a significant effect of satisfaction on the loyalty of users of the Gojek application based on Gofood. Of all the variables show that the contribution. However, the dominating variable is the service quality variable with the largest significant value.